Analysis of the Effect of Process Standards and Assessment Standards on Economic Learning Achievement through Learning Motivation of Assalam Sukoharjo High School Students - Fadlilah, Farida; Martono, Trisno; Sawiji, Hery (Budapest International Research and Critics University, 2022)
This study aims to analyze 1) the effect of process standards on student economic learning achievement, 2) the effect of assessment standards on student economic learning achievement, 3) the effect of learning motivation on student economic learning achievement, and 4) the influence of process standards and assessment standards on learning achievement economics through student learning motivation. This study uses survey research methods as a data collection tool. The sampling technique used is probability sampling, the type of simple random sampling. The sample in this study were students of Assalam High School Sukoharjo, Central Java, Indonesia, who took part in economics lessons, totaling 103 students. Research data were analyzed quantitatively using path analysis. Based on the results of the research and discussion, the researcher concludes that 1) process standards have a positive and significant effect on students' economic learning achievement; 2) assessment standards have a positive and significant effect on students' economic learning achievement; 3) learning motivation has a positive and significant effect on student achievement; and 4) process standards and assessment standards have a significant effect on economic learning achievement through student learning motivation.